Dampak model problem based learning pada kemampuan pemecahan masalah matematis - Farwati, Serlin; Sariningsih, Ratna; Hendriana, Heris (IKIP Siliwangi, 2024)
The motivation behind this investigation was the weak performance of children in math problems. The purpose of this study is to determine the impact of problem-based learning model on improving students' ability to solve mathematical problems. This study utilized a quasi-experiment method with a Nonequivalent Control Group design. The subjects in this study were class VII B as the experimental group and class VII C as the control group. Each of the two classes had thirty-five students. The purpose of using a control group as a comparison is to observe what symptoms appear in the group of participants who receive treatment. The conclusion shows that the Problem Based Learning model has a significant impact on the average N-Gain score based on the variation between the pretest score and the final score, namely the posttest score, where the average N-Gain score of the experimental and control classes is significantly different.